2013
DOI: 10.1159/000346157
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendroglial Alterations and the Role of Microglia in White Matter Injury: Relevance to Schizophrenia

Abstract: Schizophrenia is a chronic and debilitating mental illness characterized by a broad range of abnormal behaviors, including delusions and hallucinations, impaired cognitive function, as well as mood disturbances and social withdrawal. Due to the heterogeneous nature of the disease, the causes of schizophrenia are very complex; its etiology is believed to involve multiple brain regions and the connections between them, and includes alterations in both gray and white matter regions. The onset of symptoms varies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0
13

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(124 citation statements)
references
References 310 publications
2
106
0
13
Order By: Relevance
“…These proteins were previously found differentially expressed in other schizophrenia brain regions [10,32,39], a finding that is in line with evidence at the transcriptome [40,41] and morphological levels [42,43]. The differential expression of MBP and MOG supports the idea that a degenerative process might be occurring in schizophrenia brains [10,[44][45][46]. Also, MBP and MOG might be biomarker candidates to be further investigated in combination with other potential biomarkers, since they were found in different concentrations in the cerebrospinal fluid (CSF) of living schizophrenia patients [23].…”
Section: Resultssupporting
confidence: 83%
“…These proteins were previously found differentially expressed in other schizophrenia brain regions [10,32,39], a finding that is in line with evidence at the transcriptome [40,41] and morphological levels [42,43]. The differential expression of MBP and MOG supports the idea that a degenerative process might be occurring in schizophrenia brains [10,[44][45][46]. Also, MBP and MOG might be biomarker candidates to be further investigated in combination with other potential biomarkers, since they were found in different concentrations in the cerebrospinal fluid (CSF) of living schizophrenia patients [23].…”
Section: Resultssupporting
confidence: 83%
“…Recent research has demonstrated that inflammatory markers, including proinflammatory cytokines and chemokines, are associated with several pathophysiological functions, including a neuromodulatory effect on the central nervous system (CNS) [28]. Animal models suggest that the immune system is a vital component for modulating the CNS [29]. In such studies, specific cytokines, such as IL-6 and TNF-α, are shown to modulate learning, memory, and synaptic plasticity [30].…”
Section: Discussionmentioning
confidence: 99%
“…55,56 Similarly, nongenetic developmental models also result in altered prefrontal PVI. 57,58 Oligodendrocyte/Myelination Impairment Convergent evidence points to oligodendrocytes and myelination defects in SZ [59][60][61] both at the neurocytochemical and transcriptomic, as well as neuroimaging levels. Structural alterations of myelinated fibers are reported in gray and white matter of PFC and caudate nucleus of patients.…”
Section: Pvi/pnn Impairmentmentioning
confidence: 99%